Visualisasi Data Interaktif untuk Analisis Tren Stunting Pendek dan Sangat Pendek pada Balita di Kabupaten Pringsewu - Aminudin, Nur; Andriyanto, Sigit; Muharni, Sita; Feriyanto, Dwi (Metta : Jurnal Ilmu Multidisiplin, 2025)
Stunting in toddlers is a significant public health challenge in Indonesia, including in Pringsewu Regency. Conventional stunting data reporting still relies on static tables and simple graphs, which limits data exploration for policymakers. This study aims to develop interactive data visualization to analyze trends of short and very short stunting at the sub-district level during the period 2021–2023. The research methods include secondary data collection, data cleaning, and the development of an interactive dashboard using Tableau and Power BI. The results show variations in trends across sub-districts, with some sub-districts such as Pardasuka sub-district experiencing a significant decline, while others like Ambarawa sub-district saw an increase in stunting rates. Compared to conventional methods, the developed interactive visualization enables deeper data exploration through dynamic charts, thematic maps, and more intuitive comparative analysis. This facilitates policymakers in identifying priority areas and designing more effective data-driven interventions. The main contribution of this study is the provision of a more comprehensive and flexible visual-based analysis tool compared to the static methods previously used in stunting reporting.